2015
DOI: 10.5194/cp-11-1527-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying molecular oxygen isotope variations during a Heinrich stadial

Abstract: Abstract. δ 18 O of atmospheric oxygen (δ 18 O atm ) undergoes millennial-scale variations during the last glacial period, and systematically increases during Heinrich stadials (HSs). Changes in δ 18 O atm combine variations in biospheric and water cycle processes. The identification of the main driver of the millennial variability in δ 18 O atm is thus not straightforward. Here, we quantify the response of δ 18 O atm to such millennial events using a freshwater hosing simulation performed under glacial bounda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 148 publications
(201 reference statements)
0
25
0
Order By: Relevance
“…Many studies of Dole effect variability over the last glacial cycle (e.g., Bender et al, 1994;Severinghaus et al, 2009;Landais et al, 2010) have identified low-latitude precipitation as a key driver, based on coherence with orbital precession and atmospheric methane as well as high correlation with Chinese stalagmite δ 18 O. A recent quantitative, earth-system-model-based analysis of Dole effect variations over a simulated HS corroborates the hypothesized influence of low-latitude precipitation and finds that the increase in δ 18 O atm over a HS can be explained almost entirely by changes in terrestrial oxygen production-weighted δ 18 O precip (Reutenauer et al, 2015). Reutenauer et al (2015) find that oxygen production-weighted relative humidity stays effectively constant between HS and background glacial conditions.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Many studies of Dole effect variability over the last glacial cycle (e.g., Bender et al, 1994;Severinghaus et al, 2009;Landais et al, 2010) have identified low-latitude precipitation as a key driver, based on coherence with orbital precession and atmospheric methane as well as high correlation with Chinese stalagmite δ 18 O. A recent quantitative, earth-system-model-based analysis of Dole effect variations over a simulated HS corroborates the hypothesized influence of low-latitude precipitation and finds that the increase in δ 18 O atm over a HS can be explained almost entirely by changes in terrestrial oxygen production-weighted δ 18 O precip (Reutenauer et al, 2015). Reutenauer et al (2015) find that oxygen production-weighted relative humidity stays effectively constant between HS and background glacial conditions.…”
Section: Discussionmentioning
confidence: 58%
“…Modeling results from a recent freshwater hosing experiment suggest that changes in δ 18 O atm over a HS are dominated by changes in δ 18 O precip over the terrestrial biosphere (Reutenauer et al, 2015). In terms of Eq.…”
Section: The Siple Dome and Wais Divide Ice Coresmentioning
confidence: 99%
See 2 more Smart Citations
“…Again the δ 18 O atm signal over these two terminations parallels the calcite δ 18 O signals of Chinese speleothems. Following this finding, Reutenauer et al (2015) used outputs from coupled climate model and atmospheric general circulation model equipped with water isotopes to estimate the change of δ 18 O atm induced by a freshwater input. These calculations show that the increase of δ 18 O atm during a Heinrich event is induced by a southward shift of the ITCZ associated with the freshwater input leading to an increase of the δ 18 O of the low-latitude meteoric water in the Northern Hemisphere.…”
Section: δOmentioning
confidence: 99%